Analisis Unsur yang berperan terhadap Repurchase Intention - Azqia, Syfa Nur; Danibrata, Aulia (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study was to determine the effect of brand positioning, brand image, and perceived price on repurchase intention for certain products. The design of this thesis research uses descriptive research and causality research, measurement of each variable using a Likert scale with 5 points. This research takes primary data by collecting questionnaire data. This study used a purposive sampling method and obtained 252 respondents. The results of this study indicate that there is a positive influence on brand positioning, brand image, and perceived price on repurchase intention for certain products of fast food.